Pengaruh Employee Engagement, Masa Kerja, Lingkungan, Dan Kesejahteraan Terhadap Produktivitas Dengan Kepuasan Kerja Sebagai Intervening - lasmi, lasmi frina suparingga; Kemalasari, Mareta; Syaputra, Syailendra Eka (Jurnal Ekonomi STIEP, 2025)
This study aims to analyze: 1) the effect of employee engagement on job satisfaction, 2) the effect of tenure on job satisfaction, 3) the effect of work environment on job satisfaction, 4) the effect of employee welfare programs on job satisfaction, 5) The effect of employee engagement on employee work productivity with job satisfaction as an intervening variable, 6) The effect of tenure on employee work productivity with job satisfaction as an intervening variable, 7) The effect of work environment on employee work productivity through job satisfaction as an intervening variable, 8) The effect of service programs on employee work productivity with job satisfaction as an intervening variable, 9) The effect of job satisfaction on work productivity. This type of research is quantitative research, the population in the study were all employees who worked at the West Sumatra Province BKKBN office according to positions in 2023 / 2024, totaling 77 employees. The sampling technique is total sampling because the research population is less than 100, namely 77 respondents. The results showed that: First, employee engagement has a positive and significant effect on job satisfaction, with a coefficient value of 0.199 with a tcount> ttable (-4.254) > and ttable(1667) and Sig (0.000) > Alpha (0.05), meaning that H0 is rejected andHa is accepted, secondly, tenure has a positive and significant effect on job satisfaction with a coefficient value of 0.440 with atcount>ttable value (8.653) > and ttable(1667) and Sig (0.000) > Alpha (0.05), meaning that H0 is rejected andHa is accepted, the third work environment has a positive and significant effect on job satisfaction with a coefficient value of 0.790 with a tcount> ttable (15.683) > and ttable(1667) and Sig (0.000) > Alpha (0.05), meaning that H0 is rejected andHa is accepted, the fourth employee welfare program has a positive and significant effect on job satisfaction with a coefficient value of 0.210 with a tcount> ttable value (-3.667) > and ttable(1667) and Sig (0.000) > Alpha (0.05), meaning that H0 is accepted andHa is rejected, fifthemployee engagement has a positive and significant effect on employee work productivity with the research results that thetcount value (2.385) > and ttable(1.993), the sixth tenure has a positive and significant effect on employee work productivity with the research result that the coefficient value is 0.075 withtcount(3.634) > and ttable(1.667), the seventhwork environment has a positive and significant effect on employee work productivity with the value oftcount(18.680) > and ttabel (1.667), the seventhwork environment has a positive and significant effect on employee work productivity with the value oftcount(18.680) > and t table (1,667), the eighth employee welfare program has a positive and significant effect on employee work productivity as evidenced by the research results that the coefficient value is 0.171 with atcount(7.369)> and t table (1.667). and t table(1,667), the ninthjob satisfaction (X5) has a positive and significant effect on employee work productivity (n with the results of research stating that the coefficient value of 0.702tcount(38,769) > and t table(1,667) and Sig (0.000) < Alpha (0.05).